Development and transferability of microsatellite markers in Habenaria nuda and H. repens (Orchidaceae) - Vale, Aline Amalia do; Lau, Bruna Ladeira; Santos Leal, Barbara Simoes [UNESP]; Nogueira Batista, Joao Aguiar; Borba, Eduardo Leite; Proite, Karina (Soc Botanica Sao Paulo, 2016)
We report here the first set of microsatellite markers developed for species of Habenaria. A set of microsatellite markers for Habenaria nuda Lindl. and H. repens Nutt. were isolated, characterized, and tested for cross-amplification between these congeneric species. These species constitute two of the many existing complexes of the genus Habenaria. A total of nine markers were isolated from both species and characterized in two populations of each, with some of the markers being successfully cross-amplified. The numbers of alleles per locus ranged from four to 12 in H. nuda, and the mean numbers of alleles per locus were 6.0 and 6.14 in each of the populations analyzed. The observed (Ho) and expected (He) heterozygosities within the two populations varied from 0.294 to 0.850 and from 0.517 to 0.851, respectively. The numbers of alleles per locus ranged from four to seven in H. repens, and the mean numbers of alleles per locus were 2.8 and 4.0 in each of the populations analyzed. The Ho ranged from 0.000 to 0.563, and the He ranged from 0.000 to 0.666. The polymorphism levels found indicate these markers as powerful tools for future population genetic analyses in these and related species and could be used to address ecological, evolutionary, and taxonomic questions.
Keywords: Genetic diversity; Habenaria; Microsatellite markers; SSR; Transferability